Pengaruh Profitabilitas, Leverage, Likuiditas, Kualitas Audit Dan Agresivitas Pajak Terhadap Manajemen Laba Pada Perusahaan Sektor Keuangan Yang Terdaftar Di BEI Tahun 2018 – 2021 - Marcces Christine Harapan; Wenny Wenny; Deasy Arisandy Aruan; Nurganda Siregar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research was formulated whether or not there are influence of probability, leverage, liquidity, audit quality and tax aggressiveness toward earnings management in financial sector companies listed on the idx 2019-2021. The purpose of the research was to figure out the are influence of probability , leverage, liquidity, audit quality and tax aggressiveness toward earnings management in financial sector companies listed on the idx 2019-2021. This type of research used a quantitative descriptive type. The variables of this research were probability, leverage, liquidity, audit quality, tax aggressiveness and earnings management. The data collection technique used was the documentation method. The documentationmethod was used as the basis for analyzing the data. The documentation was in the form of financial report. The analysis technique used in this research was multiple linear regression analysis. The results of the test for coefficient of determintation obtained an R square result of 0,006 or 6%, which means that the influence of probability, leverage, liquidity, audit quality and tax aggressiveness toward earnings management wasn’t too large. The results showed that probability, liquidity, audit quality and tax aggressiveness had no effect on earnings management, while leverage had an effect on earnings management.